POTENSI TUMBUHAN BAWAH SEBAGAI TANAMAN HIAS DI KAWASAN AIR TERJUN SARAMBU’ALLA KABUPATEN LUWU UTARA - Uci Angraini; Yumna Yumna; Witno Witno (Jurnal Penelitian Kehutanan BONITA, 2022)
The village Kalotok is one of the villages which is located in the District of Sabbang South, North Luwu Regency, with an area of 4,500 ha, of which the majority of its territory is in the mountains and rural, which has a variety of types of vegetation understorey. The understorey has a significant role in the ecosystem; one of the species below is an ornamental plant that has influence directly on human ecology, is used to set the erosion and wind, to give your device a place of recreation and sports as well as for satisfying the human desire on beautiful objects. This study aims to determine the types of plants under potential as ornamental plants in the waterfall Sarambu'alla. Pengamatan is done by using the technique of purposive sampling and laying a plot on the location of widely scattered understorey potential as an ornamental plant. The Plot of the study size is 20 m x 20 m with the consideration of the area of The Waterfall 58.000 m2, so that the intensity of sampling for research by 10% with an area of 5,800 m2, so that the total plot research 15 plots with an area of 6000 m2. Data analysis used is the analysis of the important values to calculate the value of the density, relative density, frequency, and relative frequency. This study found 12 types of plants with an overall total of 1487 individuals. The amount of the highest kind is Paku Rene (Selaginella), while the number of the type has the lowest value, i.e. Sirih Lurik (Scindapsus pictus). The important values in the category of excellent (160) this value into the potential to increase the income of economic value to the community if appropriately utilised.